Microstructural evolution in AISn-based gas atomised powder and thermally sprayed coatings - Kong, Chang Jing (2004)
This thesis reports on the microstructure of AI-Sn based powders and the development of AI-Sn based coatings for automotive shell bearing applications deposited using the high velocity oxy-liquid fuel (HVOLF) thermal spray technique. The microstructure of the coating and its associated physical and chemical properties, such as microhardness and corrosion resistance, are investigated as a function of the HVOLF thermal spraying parameters. In particular, a detailed microstructural understanding of the thermal sprayed coatings is developed to explain the coating properties.